Analisis Kemampuan Membaca Permulaan Dalam Pembelajaran Tematik pada Siswa Kelas I SD Negeri 68 Palembang - Anggrarini, Ramni; Misdalina, Misdalina; Hera, Treny (ANTHOR: Education and Learning Journal, 2022)
The purpose of this study was to determine the initial reading ability in thematic learning of grade 1 students at SD Negeri 68 Palembang and to describe students' reading difficulties. The approach used in this research is descriptive qualitative using data collection techniques in the form of observation, interviews, tests and documentation. Check the validity of the data using triangulation. Data were analyzed through data collection steps such as data reduction, data presentation, and drawing conclusions. The results showed that the reading ability of grade 1 students showed that 3 out of 24 students were low in starting reading. In this preliminary reading, it is divided into three categories, namely the ability to read the beginning of the very good category, the beginning reading of the moderate category and the early reading of the poor category. The difficulties found by the researchers in the process of learning to read the beginning were that these students had almost the same reading difficulties, namely not understanding the letters of the alphabet, not being able to distinguish between vowels and consonants, halting in reading, having difficulty connecting sentences and reading completely.